Effects of Escherichia coli hemolysin on endothelial cell function. - Suttorp, N (1990)
Escherichia coli hemolysin is considered an important virulence factor in extraintestinal E. coli infections. The present study demonstrates that cultured pulmonary artery endothelial cells are susceptible to attack by low concentrations of E. coli hemolysin (greater than or equal to 0.05 hemolytic units/ml; greater than or equal to 5 ng/ml). Sublytic amounts of hemolysin increased the permeability of endothelial cell monolayers in a time- and dose-dependent manner. The hydraulic conductivity increased approximately 30-fold and the reflection coefficient for large molecules dropped from 0.71 to less than 0.05, indicating a toxin-induced loss of endothelial barrier function. The alterations of endothelial monolayer permeability were accompanied by cell retraction and interendothelial gap formation. In addition, E. coli hemolysin stimulated prostacyclin synthesis in endothelial cells. This effect was strictly dependent on the presence of extracellular Ca2+ but not of Mg2+. An enhanced passive influx of 45Ca2+ and 3H-sucrose but not of tritiated inulin and dextran was noted in toxin-treated cells, indicating that small transmembrane pores comparable to those detected in rabbit erythrocytes had been generated in endothelial cell membranes. These pores may act as nonphysiologic Ca2+ gates, thereby initiating different Ca2+-dependent cellular processes. We conclude that endothelial cells are highly susceptible to E. coli hemolysin and that two major endothelial cell functions are altered by very low concentrations of hemolysin.